Single Source of Truth dalam Coretax dan Implikasinya terhadap Tanggung Jawab Direktorat Jenderal Pajak sebagai Pengendali Data Pribadi - Surya Marathonsi; Agus Ariadi (Insight: Indonesian Journal of Social, Humanity, and Education, 2026)
The Single Source of Truth (SSOT) is the latest breakthrough and a strategic initiative by the Directorate General of Taxes, built upon four pillars: Social Business, Mobile, Cloud Computing, and Big Data Analysis. The implementation of this Single Source of Truth raises the question of the Directorate General of Taxes’ accountability as the controller of personal data from the perspective of the Personal Data Protection Act. This article was written to analyze the implications of the Single Source of Truth for the Directorate General of Taxes in managing taxpayer data, and how Coretax manages its legal responsibilities. The research employs a legislative and conceptual approach using normative legal methodology. The study concludes that the Directorate General of Taxes bears full responsibility for the confidentiality and processing of personal data and is obligated to demonstrate its accountability in implementing the principles of Personal Data Protection. Given the challenges posed by gaps in technical regulations and the absence of an independent supervisory authority within Indonesia’s civil law system, this study contributes theoretically to the development of the doctrine of state accountability and public data controller responsibilities in digital tax administration. Practically, this study provides strategic insights for tax authorities, policymakers, and practitioners to strengthen compliance with the law. [Single Source of Truth (SSOT) atau sumber data tunggal merupakan terobosan teranyar sekaligus langkah strategis Direktorat Jenderal Pajak yang dibangun diatas empat pilar: Social Business, Mobile, Cloud Computing, dan Big Data Analysis. Implementasi dari sumber data tunggal ini kemudian menghadirkan suatu pertanyaan bagaimana Akuntabilitas Direktorat jenderal Pajak yang merupakan pengendali data pribadi dari sudut pandang kacamata Undang-Undang Pelindungan Data Pribadi. Artikel ini ditulis dalam rangka analisis konskuensi Single Source of Truth pada Direktorat Jenderal Pajak dalam mengendalikan data wajib pajak, dan bagaimana pengelolaan tanggung jawab hukum Coretax. Penelitian menggunakan pendekatan perundang-undangan dan konseptual dengan metode yuridis normatif. Penelitian menyimpulkan bahwa Direktorat Jenderal Pajak bertanggung jawab penuh atas kerahasiaan, pemrosesan data pribadi sekaligus wajib menunjukkan pertanggungjawabannya dalam pelaksanaan prinsip Pelindungan Data Pribadi. Dengan situasi adanya tantangan kekosongan aturan teknis dan ketiadaan lembaga otoritas pengawas independen dalam sistem hukum civil law di Indonesia, penelitian ini berkontribusi secara teoretis dalam mengembangkan doktrin akuntabilitas negara dan pengendali data publik pada administrasi perpajakan digital. Secara praktis, penelitian ini memberikan masukan strategis bagi otoritas pajak, pembuat kebijakan, dan praktisi guna memperkuat kepatuhan terhadap undang-undang.]